Application of nano titanium dioxide in degradation of volatile phthalate in air

By using the catalytic activity of nano -titanium dioxide to adsorb and hydrolyze the volatile tunterite in the air, it solves the problem of difficulty to quickly degrade pollutants in the air in the existing technology, realizes high -efficiency degradation and recycling, avoiding pollution The second release of things.

CN119345901APending Publication Date: 2025-01-24NANJING UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411608439.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The prior art is difficult to quickly and effectively degrade volatile phthalate in the air, and traditional adsorption methods are difficult to avoid secondary release of pollutants.

Method used

Using nano -titanium dioxide, by regulating its crystal structure, it enhances its catalytic activity, adsorb and hydrolyze the volatile phenyl acid ester in the air to form a mineralized degradable product, and uses light treatment to achieve circulating of nano -titanium dioxide. Essence

Benefits of technology

It achieves rapid adsorption and hydrolysis of volatile phthalates in the air under low humidity conditions, with high degradation efficiency, avoids the secondary release of pollutants, and realizes the recycling of nano-titanium dioxide through light treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119345901A_ABST
    Figure CN119345901A_ABST
Patent Text Reader

Abstract

The invention discloses an application of nano titanium dioxide in degradation of volatile phthalic acid ester in air, which comprises the following steps: placing nano titanium dioxide in the air containing volatile phthalic acid ester, and carrying out adsorption and degradation reaction under the condition that the relative humidity of the air is 1-40%, a degradation product formed after the reaction is completed is removed through illumination treatment mineralization, and the nano titanium dioxide is recycled. The nano titanium dioxide is simple to synthesize, low in cost, capable of being synthesized in a large scale and recycled, and capable of adsorbing and hydrolyzing volatile phthalate in air and avoiding secondary release of pollutants, and meanwhile, degradation products of the phthalate occupy active sites on the surface of the titanium dioxide, so that the photocatalytic activity of the nano titanium dioxide is improved, and the service life of the nano titanium dioxide is prolonged. Titanium dioxide is used as one of typical semiconductor materials, and pollutants can be mineralized through illumination to recover active sites, so that the titanium dioxide can be recycled.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to air pollutant treatment, and in particular to the application of nano titanium dioxide in degrading volatile phthalates in the air. Background Art

[0002] Phthalates contain a rigid planar benzene ring and two linear aliphatic chains. They are colorless, low-volatile, poorly water-soluble synthetic organic compounds. Because phthalates can promote the transparency, strength, plasticity and durability of materials, they are commonly used in plastics, fertilizers, pesticides, toys, cosmetics and other industries. However, phthalates only interact with polymer molecules in a non-covalent manner and are easily released during the aging process of plastics, causing widespread environmental pollution. Phthalates are often detected in surface water, soil and sludge, and their concentration in indoor air can reach 25,000 ng / m 3 Phthalates are endocrine disruptors. Long-term exposure to high concentrations of phthalates can cause serious damage to the respiratory, reproductive and endocrine systems of the human body. Based on this, it is necessary to develop efficient, stable and environmentally friendly technology to treat air containing phthalates.

[0003] Phthalates are removed very slowly through natural processes such as hydrolysis and photolysis. At present, there is a lack of technologies and methods for the rapid degradation of phthalates in the air. Microbial degradation, photocatalytic degradation, advanced oxidation processes and electroremediation can effectively degrade phthalates in soil and water. However, these methods are difficult to apply in air environments. Biochar and metal organic frameworks can adsorb phthalates in the air, but they cannot degrade them, which means that the adsorbed biochar and metal organic frameworks need to be properly disposed of, otherwise it will cause secondary release of phthalates. Summary of the invention

[0004] Purpose of the invention: The purpose of the present invention is to provide an application of nano titanium dioxide with high degradation efficiency and recyclability in degrading volatile phthalates in the air.

[0005] Technical solution: The application of the nano titanium dioxide in the degradation of volatile phthalates in the air of the present invention comprises the following steps: placing the nano titanium dioxide in the air containing volatile phthalates, carrying out adsorption and degradation reaction under the condition of relative humidity of 1-40%, removing the degradation products formed after the reaction by mineralization through light treatment, and the nano titanium dioxide is recycled.

[0006] Furthermore, the relative humidity of the air is preferably 5-33%.

[0007] Furthermore, the nano-titanium dioxide is a rhombic titanium dioxide nanoparticle with a crystal face of {101}, a rod-shaped titanium dioxide nanoparticle with a crystal face of {010}, or a plate-shaped titanium dioxide nanoparticle with a crystal face of {001}. Preferably, the nano-titanium dioxide is a plate-shaped titanium dioxide nanoparticle with a crystal face of {001}.

[0008] Furthermore, the volatile phthalate is dimethyl phthalate.

[0009] Furthermore, the application method may also include the following steps: loading nano titanium dioxide on a carrier and placing it in air containing volatile phthalates to perform adsorption and degradation reactions under light conditions; the light conditions are: light power of 100-500mW / cm 2 , the relative humidity of air is 10-90%, and the temperature is 20-40° C.; the carrier is silicon dioxide particles.

[0010] Principle of the invention: The present invention utilizes inorganic or organic ions combined with specific crystal faces to achieve the synthesis of high-energy surface titanium dioxide nanoparticles, and exhibits excellent catalytic activity. The face-regulated titanium dioxide surface has abundant Lewis acid sites, which can not only coordinate with the carbonyl oxygen of dimethyl phthalate to adsorb volatile dimethyl phthalate, but also accelerate the hydrolysis reaction process to generate monomethyl phthalate, which is then further hydrolyzed into phthalic acid. In particular, the TiO2-{101}, {010} and {001} surfaces all have Ti-Ti sites with adjacent spacing of 0.38 nm, which can be bidentately coordinated with the diester group of dimethyl phthalate, which can greatly enhance the Lewis acid catalysis. The hydrolysis rate of dimethyl phthalate on the TiO2-{101}, {010} and {001} surfaces is related to the surface probability Ti-Ti bidentate site density (D p-bi ). In addition, water molecules will compete for the active sites on the titanium dioxide surface. When the relative humidity is low, the first layer of water molecules is not formed on the TiO2-{101}, {010} and {001} surfaces. The TiO2-{001} surface tends to dissociate water molecules in its first hydration layer, resulting in a disordered hydrogen bond network, allowing dimethyl phthalate to compete for reaction sites. The resulting hydrolysis products such as monomethyl phthalate and phthalic acid will occupy the surface active sites. When adsorbed sufficiently, the hydrolysis performance of titanium dioxide is lost. Considering that titanium dioxide is a typical semiconductor that can produce ·OH and ·O2 under light - To oxidize organic pollutants into CO2 and H2O, thereby releasing surface Lewis acid sites, which makes it possible to recycle titanium dioxide.

[0011] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: (1) The three single crystal face-regulated nano-titanium dioxide provided by the present invention has a larger specific surface area and more active sites. Under certain temperature and low humidity air conditions, it can quickly adsorb and hydrolyze dimethyl phthalate in the air. The preparation cost is low and it has the potential for mass production; (2) Dimethyl phthalate and its hydrolysis products dimethyl phthalate and phthalic acid can be well adsorbed on the surface of titanium dioxide to avoid the secondary release of pollutants; (3) The hydrolysis products of phthalates will occupy the active sites on the surface of titanium dioxide. Titanium dioxide, as one of the typical semiconductor materials, can recover the active sites by degrading pollutants through light irradiation, thereby being recycled. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 The scanning electron microscope images of three nano-titanium dioxide materials prepared in Example 1, wherein (a) is a rhombus-shaped titanium dioxide nanoparticle, (b) is a rod-shaped titanium dioxide nanoparticle, and (c) is a plate-shaped titanium dioxide nanoparticle;

[0013] Figure 2 The transmission electron micrographs of three nano-titanium dioxide materials prepared in Example 1, wherein (a) is a rhombus-shaped titanium dioxide nanoparticle, (b) is a rod-shaped titanium dioxide nanoparticle, and (c) is a plate-shaped titanium dioxide nanoparticle;

[0014] Figure 3 The high-resolution transmission electron micrographs of three nano-titanium dioxide materials prepared in Example 1 are shown, wherein (a) is a rhombus-shaped titanium dioxide nanoparticle, (b) is a rod-shaped titanium dioxide nanoparticle, and (c) is a plate-shaped titanium dioxide nanoparticle.

[0015] Figure 4 The hydrolysis reaction kinetic curve of the diamond-shaped nano-titanium dioxide particles (TiO2-{101}) in Example 1 to directly added DMP at air humidity of <10%, 33%, 76% and 100%;

[0016] Figure 5 The hydrolysis reaction kinetic curve of rod-shaped nano titanium dioxide particles (TiO2-{010}) in Example 1 to directly added DMP at air humidity of <10%, 33%, 76% and 100%;

[0017] Figure 6 The hydrolysis reaction kinetic curve of plate-like nano-titanium dioxide particles (TiO2-{001}) in Example 1 to directly added DMP at air humidity of <10%, 33%, 76% and 100%;

[0018] Figure 7The kinetic curve of the diamond-shaped nano-titanium dioxide particles (TiO2-{101}) in Example 1 adsorbing and hydrolyzing the volatilized DMP at 33% air humidity;

[0019] Figure 8 The kinetic curve of the adsorption and hydrolysis of volatile DMP by rod-shaped nano titanium dioxide particles (TiO2-{010}) in Example 1 at 33% air humidity;

[0020] Fig. 9 The kinetic curve of the plate-like nano titanium dioxide particles (TiO2-{001}) in Example 1 adsorbing and hydrolyzing the volatilized DMP at 33% air humidity;

[0021] Fig.10 The kinetic curve diagram of photocatalytic degradation of MMP by three nano-titanium dioxide particles in Example 1 under 10% air humidity;

[0022] Fig.11 The kinetic curve diagram of photocatalytic degradation of MMP by three nano-titanium dioxide particles in Example 1 under 90% air humidity;

[0023] Fig.12 The kinetic curve of photocatalytic degradation of DMP, MMP and PA by diamond-shaped nano-titanium dioxide particles (TiO2-{101}) in Example 2 at 90% air humidity;

[0024] Fig.13 The kinetic curve of photocatalytic degradation of DMP, MMP and PA by rod-shaped nano-titanium dioxide particles (TiO2-{010}) in Example 2 at 90% air humidity;

[0025] Fig.14 This is a kinetic curve of the photocatalytic degradation of DMP, MMP and PA by plate-like nano-titanium dioxide particles (TiO2-{001}) in Example 2 at 90% air humidity. DETAILED DESCRIPTION

[0026] The present invention is further described below in conjunction with specific embodiments and drawings.

[0027] Example 1: The application of nano-titanium dioxide provided in this example to degrade volatile phthalates in the air, wherein the volatile phthalate is dimethyl phthalate; the nano-titanium dioxide is rhombic titanium dioxide nanoparticles with a crystal face of {101}, rod-shaped titanium dioxide nanoparticles with a crystal face of {010}, or plate-shaped titanium dioxide nanoparticles with a crystal face of {001}.

[0028] The preparation method of the above-mentioned rhombic titanium dioxide nanoparticles (TiO2-{101}) comprises the following steps:

[0029] (1) Add 4g of nano titanium dioxide particles (anatase type) to 160ml of 17mmol / mL KOH solution, pour the solution into a high-pressure reactor for sealed reaction, the reaction temperature is 110℃, and the reaction time is 20h. Wash the reaction solution with pure water for several times, and collect the precipitate by centrifugation. Then add the precipitate to 400mL of 1mmol / mL acetic acid solution, ultrasonically treat for 30min, let it stand for 2h, wash the reaction solution with pure water for several times, collect the white powder by centrifugation, and dry it in an oven at 80℃;

[0030] (2) Add 0.7 g of white powder to 210 mL of pure water, stir at room temperature for 30 min, pour the solution into a high-pressure reactor for sealed reaction, the reaction temperature is 170° C., and the reaction time is 24 h. Wash the reaction solution with pure water for multiple times, collect the titanium dioxide powder by centrifugation, and dry it in an oven at 120° C.

[0031] like Figure 1-Figure 3 As shown in (a), the synthesized TiO2-{101} nanoparticles are octahedral in shape, with a length of 15 to 40 nm and a lattice fringe spacing of 0.35 nm.

[0032] The preparation method of the above-mentioned rod-shaped titanium dioxide nanoparticles (TiO2-{010}) comprises the following steps:

[0033] (1) Add 4.89g of anatase titanium dioxide powder and 112.2g of NaOH to 200mL of pure water, pour the suspension into a sealed autoclave for reaction at a temperature of 180°C for 24h. Wash and collect the white powder by centrifugation, and dry it in an oven at 80°C. Add the white powder to 400mL of 1mmol / mL HCl solution, ultrasonically treat for 30min, let stand for 2h, wash by centrifugation, and separate to obtain HTiO3 nanotubes;

[0034] (2) 1.05 g of HTiO3 nanotubes were added to 210 mL of pure water, stirred at room temperature for 30 min, and the solution was poured into a sealed autoclave for reaction at a temperature of 170°C for 16 h. The titanium dioxide powder was washed and collected by centrifugation and dried in an oven at 120°C.

[0035] like Figure 1-Figure 3 As shown in (b), the synthesized TiO2-{010} nanoparticles are rod-shaped with a lattice fringe spacing of 0.35 nm.

[0036] The method for preparing the plate-like titanium dioxide nanoparticles ({TiO2-{001}) comprises the following steps:

[0037] (1) 150 mL of tetrabutyl titanate and 18 mL of 49% HF solution were mixed and then poured into a sealed autoclave for reaction at a temperature of 200°C for 24 h. The reaction solution was washed with ethanol and pure water for several times, and the white powder was collected by centrifugation and dried in an oven at 80°C.

[0038] (2) Add 0.5 g of white powder to 100 mL of 0.1 mmol / mL NaOH solution and stir at room temperature for 12 h. Wash and collect the titanium dioxide powder by centrifugation and dry it in an oven at 120°C.

[0039] like Figure 1-Figure 3 As shown in (c), the synthesized TiO2-{001} nanoparticles are plate-like in shape with a length of 40 to 60 nm and a thickness of 6 nm.

[0040] Test 1: The degradation performance of the three nano-titanium dioxide particles mentioned above for dimethyl phthalate (DMP) was tested at different relative air humidity. The steps are as follows:

[0041] Pour 50 mg of TiO2-{101}, {010} and {001} into a glass bottle, add 200 μL of 0.5 mM DMP acetone solution respectively, control the DMP concentration to 2.0 μmol / g, and place it away from light for 1 hour. After the acetone evaporates, transfer the glass vial to a dryer at 25°C, pre-add P2O5 powder or saturated MgCl2 solution to the bottom of the dryer, and control the humidity in the dryer to be constant at <10% and =33%, respectively. Under low relative humidity, more active sites can be exposed on the surface of titanium dioxide. By pre-adding saturated NaCl and pure water solution to the bottom of the dryer, the humidity in the dryer was controlled to be constant at =76% and =100%, respectively, as a control group. Under high relative humidity, the active sites on the surface of titanium dioxide are basically completely covered.

[0042] After a certain period of reaction, sampling was carried out, and a methanol / water solution (containing 4 mM EDTA, pH = 10) with a volume ratio of 1:1 was used as an extractant. DMP and its products were extracted by oscillation with 5 mL of the extract, filtered through a 0.45 μm polytetrafluoroethylene filter membrane, and then 100 μL of 1 M HClO4 solution was added, and the concentration was determined by liquid chromatography.

[0043] Experimental results: Figure 4 , Figure 5 and Figure 6As shown in the figure, under low humidity (RH<10% and =33%), DMP can be significantly degraded into monomethyl phthalate (MMP) on TiO2-{101}, {010} and {001}, and the secondary hydrolysis product phthalic acid (PA) is also detected. On the contrary, under high humidity (RH=76% and =100%), only a small amount of DMP hydrolysis product is detected. The mass balance of reactants and products reaches more than 90%, indicating that DMP is mainly hydrolyzed on the TiO2 surface rather than adsorbed. Under RH=33%, the hydrolysis half-life (t 1 / 2 ) are 0.294, 0.263 and 0.075 days. Under RH = 100%, the hydrolysis half-life (t1 / 2) of DMP on TiO2-{101}, {010} and {001} are 20.63, 12.53 and 54.15 days. After normalization by specific surface area, under RH = 33%, the hydrolysis rate constants of DMP on TiO2-{101}, {010} and {001} are 42.13, 38.85 and 145.15 kg·day, respectively. -1 ·m -2 This indicates that TiO2-{101}, {010}, and {001} have the potential to rapidly degrade DMP under low humidity conditions.

[0044] Test 2: Under the condition of 33% relative humidity, the above three nano-titanium dioxide particles were tested for their ability to adsorb and degrade DMP in the air. The steps are as follows:

[0045] 50 mg of TiO2-{101}, {010} and {001} were poured into a glass bottle, which was opened and placed in a desiccator. Saturated MgCl2 solution was added to the bottom of the desiccator in advance, and the humidity in the desiccator was controlled to be constant at 33%. At the same time, a small bottle containing pure DMP was opened and placed in a desiccator. The temperature was controlled at 35°C to allow DMP to evaporate in the headspace. Samples were taken intermittently during the reaction, and DMP and its products were extracted using the same extraction method as in Test 1, and then determined by liquid chromatography.

[0046] Experimental results: The accumulation of DMP on TiO2-{101}, {010} and {001} is shown in Figure 7 , Figure 8 and Fig. 9 As shown in the figure, it can be seen that they can effectively adsorb and fix volatile DMP from the headspace. The adsorption amounts of TiO2-{101}, {010} and {001} after 12 days are 66.46, 65.90 and 71.58 μmol·g, respectively. -1At the same time, the DMP adsorbed on the three materials can also be quickly hydrolyzed into low-volatile MMP and PA. Within 12 days, the degradation rates of DMP on TiO2-{101}, {010} and {001} were 93.56%, 95.23% and 98.90%, respectively. At present, the reported values ​​of PAEs pollutant concentration in indoor and plastic greenhouse air are in the range of 10 to 1000 ng / m3. It is estimated that the treatment capacity of TiO2-{101}, {010} and {001} can exceed 12906m 3 ·g -1 , which is enough to meet the current general application needs. Moreover, TiO2-{001} can not only adsorb high concentrations of DMP, but also has the advantages of faster hydrolysis rate and more thorough degradation, and has a high application potential in passive treatment.

[0047] Test 3: Performance test of nano-titanium dioxide in removing MMP under light.

[0048] Under the condition of 90% relative humidity, the performance of the above three nano-titanium dioxide particles in degrading MMP was tested. 0.5g of titanium dioxide nanoparticles and 9.5g of silicon dioxide particles were poured into a glass beaker, 25mL of pure water was added and stirred for 1 day, and then dried in an oven at 60°C to obtain silicon dioxide samples loaded with TiO2-{101}, {010} and {001}. Take 0.5g of the sample in a glass vial, add 1mL of 1.25mM MMP acetone solution, oscillate for 2h in a dark environment, and then leave it open in the air until the acetone evaporates completely. The sample was spread on a glass disc with a diameter of about 5cm and placed in a photoreactor. The relative humidity in the system was controlled to be 90% and the temperature was 25°C by air bubbling and circulating cooling water. The sample was irradiated with a xenon lamp, and the light power density was controlled at 100mW / cm 2 During the reaction, samples were taken intermittently, and MMP was extracted using the same extraction method as in test 1, and its concentration was determined by liquid chromatography.

[0049] Experimental results: Fig.10 and Fig.11 As shown in Figure 2, when the loading amount of MMP was 50 μmol·g -1 When TiO2-{101}, {010} and {001} were used, they were able to almost completely degrade MMP within 1 h in a wide relative humidity range. MMP, as the main hydrolysis product of DMP, occupies the active sites on the TiO2 surface. Under light, the reactive oxygen species generated by TiO2, such as ·OH and ·O2 -It can quickly oxidize MMP to CO2 and H2O, thereby exposing the Lewis acid sites on the TiO2 surface to continue to adsorb and hydrolyze DMP in the air. Among them, when the relative humidity increases from 10% to 90%, the photocatalytic performance of TiO2-{101}, {010} and {001} all increase, which is due to the increase in the content of water molecules on the titanium dioxide surface, which promotes the generation of active oxygen species. In addition, under RH = 10% and 90%, TiO2-{001} exhibits better photocatalytic activity than TiO2-{101} and {010}, further proving the application potential of TiO2-{001}.

[0050] Experimental Example 2: Performance test of nano-titanium dioxide in removing DMP, MMP and PA under light irradiation.

[0051] Under the condition of 90% relative humidity, the three nano titanium dioxide particles prepared in Example 1 were tested for their ability to degrade DMP, MMP and PA, and the steps were as follows:

[0052] Pour 0.5g of titanium dioxide nanoparticles and 9.5g of silicon dioxide particles into a glass beaker, add 25mL of pure water and stir for 1 day, then dry in an oven at 60°C to obtain silicon dioxide samples loaded with TiO2-{101}, {010} and {001}. Take 0.5g of the sample in a glass vial, add an acetone solution containing DMP, MMP and PA, shake for 2h in a dark environment, and then leave it open in the air until the acetone evaporates completely. The concentrations of DMP, MMP and PA on the TiO2-{101} surface are controlled at 5, 50 and 12μmol·g -1 The concentrations of DMP, MMP and PA on the TiO2-{010} surface were controlled at 3, 55 and 7 μmol·g -1 The concentrations of MMP and PA on the TiO2-{001} surface were controlled at 64 and 7 μmol·g -1 The sample was spread on a glass disc with a diameter of about 5 cm and placed in a photoreactor. The relative humidity in the system was controlled to be 90% and the temperature to be 25°C by air bubbling and circulating cooling water. The sample was irradiated with a xenon lamp, and the light power density was controlled at 100 mW / cm 2 During the reaction, samples were taken intermittently, and MMP was extracted using the same extraction method as in Experimental Example 1, and its concentration was determined by liquid chromatography.

[0053] Experimental results: Fig.12 and Fig.13 , Fig.14As shown in the figure, when RH = 90%, TiO2-{101}, {010} and {001} can almost completely degrade surface-loaded DMP, MMP and PA under light within 1 h, showing excellent photocatalytic ability. When TiO2-{101}, {010} and {001} adsorb and hydrolyze volatile DMP, a small amount of DMP and PA will still be fixed on the surface, which can be removed by light.

Claims

1. Application of nano titanium dioxide in degrading volatile phthalates in the air.

2. The use according to claim 1, characterized in that: The application method comprises the following steps: placing nano titanium dioxide in air containing volatile phthalates, carrying out adsorption and degradation reaction under the condition of relative air humidity of 1-40%, and removing the degradation products formed by the reaction through mineralization by light treatment after the reaction is completed, and the nano titanium dioxide is recycled.

3. The use according to claim 2, characterized in that: The relative humidity of the air is 5-33%.

4. The use according to claim 2, characterized in that: The nano titanium dioxide is a rhombus titanium dioxide nanoparticle with a crystal face of {101}.

5. The use according to claim 2, characterized in that: The nano titanium dioxide is a rod-shaped titanium dioxide nanoparticle with a {010} crystal plane.

6. The use according to claim 2, characterized in that: The nano titanium dioxide is a plate-like titanium dioxide nanoparticle with a crystal plane of {001}.

7. The use according to claim 2, characterized in that: The volatile phthalate is dimethyl phthalate.

8. The use according to claim 1, characterized in that: The application method comprises the following steps: loading nano titanium dioxide on a carrier and placing the carrier in air containing volatile phthalates, and performing adsorption and degradation reactions under light conditions.

9. The use according to claim 8, characterized in that: The illumination conditions are: light power is 100-500mW / cm 2 .

10. The use according to claim 8, characterized in that: The carrier is silicon dioxide particles.

Citation Information

Cited By

  • Near-infrared light enzyme catalyst as well as preparation method and application thereof

    CN120648675A